Diagnostic pathology. Kidney diseases - Colvin, Robert B. (Philadelphia, PA : Amirsis/Elsevier, 2016)
"Welcome to the world of renal pathology! The team of renal pathologists who developed this book has over 250 years of combined experience in renal pathology. We are motivated by the desire to create a comprehensive, succinct, and diagnostically useful resource for practicing pathologists, nephrologists and all students of kidney diseases. Here you will find the most complete survey available of non-neoplastic diseases of native and transplant kidneys amply illustrated by over 3500 pathology images of classic and variant features. The information and images are web-accessible to all owners of the book and to subscribers of ExpertPath© by Elsevier. Renal pathologists typically consider pathogenesis and etiology, in addition to the diagnosis. This approach requires knowledge of the clinical presentation, relevant laboratory and molecular data and evidence from mechanistic research studies. We provide all of these elements in a highly structured format for each disease entity. The authors are particularly delighted to present the second edition of this text. The excellent reception to the first edition has encouraged us to update and expand the contents. We have added 40 chapters and 5 new authors, reorganized some of the sections, updated and polished text in all of the chapters and added current references and innumerable new images. Overall we are pleased that the book reflects significant progress on our quest to provide a useful, accurate and accessible compendium of all non-neoplastic renal diseases for clinicians, pathologists and investigators. One may ask why so many chapters? The answer is that medical research has led to an increasing number of distinct diseases, once categorized by clinical and pathologic characteristics, and now increasingly further defined and separated by etiologic and genetic criteria. The structured format of the book is conducive to presenting this expanding list that will continue to grow in the era of personalized medicine. We hope this text will help improve the diagnosis of renal disease and stimulate advances in the field."--Provided by publisher
Preceded by Diagnostic pathology. Kidney diseases / [edited by] Robert B. Colvin [and others]. c2011
Includes bibliographical references and index
Keywords: Kidneys -- Diseases -- Diagnosis -- Atlases; Kidney Diseases -- diagnosis; Kidney Diseases -- pathology; Print books